Information Communication Technology (ICT) and Education - Igor Balaban; Bart Rienties; Philip H. Winne (Applied Sciences, 2023)
COVID-19 has accelerated the shift to blended or fully online learning environments, enforcing educational institutions to embrace technology and offer their students an online or at least blended learning experience [...]